Inovação em micro e pequenas empresas: uma análise do caso brasileiro - Maia, Adriano Filipe da Silva (2012)
Micro and small enterprises play a key role in generating employment and income, what qualifies them as inducers of economic development. Inserted in markets increasingly competitive and globalized, the micro and small businesses increasingly rely on technological capability and the generation of innovations to ensure their survival and success. The theoretical work is based on unorthodox approaches, which give innovation a central role in economic activity. We start from the hypothesis that in Brazil there is a significant sectoral heterogeneity in relation to the characteristics of the innovative process in small enterprises. The objective is therefore to demonstrate the sectoral peculiarities of Brazilian small firms regard to the process of generation of innovations. The characterization of innovation activities is made from performance indicators of the innovative process, efforts made to innovate, cooperation and government support. The analysis of sectoral differences in innovative activity of small Brazilian companies was only possible thanks to the sending of a special tabulation of Pesquisa de Inovação Tecnológica (PINTEC) 2008 by Instituto Brasileiro de Geografia e Estatística (IBGE). Some industries such as Pharmaceuticals and Computer and electronics had rates that give a prominent position inside the universe of small businesses. In other sectors such as Wood products and Metallurgy were found relatively poor indicators. The results thus corroborate the hypothesis of sectoral heterogeneity and demonstrate the complexity of the universe of Brazilian micro and small enterprises regard to the characteristics of the innovation process.